The Effects of Influenza Vaccination during Pregnancy on Birth Outcomes: A Systematic Review and Meta-Analysis - Nunes, Marta C.; Aqil, Anushka R.; Omer, Saad B.; Madhi, Shabir A. (American Journal of Perinatology, 2016)
Objective Numerous observational studies have evaluated the relationship between influenza vaccination during pregnancy and birth outcomes. The number of studies on this subject has increased, especially after the 2009 A/H1N1 pandemic (A/H1N1pdm09). This meta-analysis aims to determine the impact of maternal vaccination with either seasonal trivalent inactivated influenza vaccines (IIV) or A/H1N1pdm09 monovalent vaccines on the rates of preterm (PTB), small for gestational age (SGA), and low birth weight (LBW) births.Methods English language randomized controlled trials and observational studies assessing the proposed outcomes after administration of influenza vaccine during pregnancy were screened. Observational studies were included if they presented adjusted measures and if the total number of women evaluated reached predefined thresholds. Sensitivity analyses were performed, including all published observational studies irrespectively of the sample size.Results A total of 5 and 13 publications that assessed the impact of IIV and monovalent A/H1N1pdm09 vaccines, respectively, fulfilled the inclusion criteria for the main analyses. The rate of PTB and LBW was lower in women who received IIV during pregnancy compared with nonvaccinated women (odds ratio [OR]: 0.87; 95% confidence interval [CI]: 0.77, 0.98 for PTB and OR: 0.74; 95% CI: 0.61, 0.88 for LBW); and in women vaccinated with monovalent A/H1N1pdm09 versus nonvaccinated women (OR: 0.92; 95% CI: 0.85, 0.99 for PTB and OR: 0.88; 95% CI: 0.79, 0.98 for LBW). No significant impact of vaccination on SGA birth rates was detected in the main analyses independently of the vaccine group.Conclusion Receipt of influenza vaccine during pregnancy was associated with a decreased risk of PTB and LBW.
Keywords: vaccine; preterm birth; small for gestational age; low birth weight; maternal immunization